2014
DOI: 10.1038/srep04690
|View full text |Cite
|
Sign up to set email alerts
|

High resolution imaging beyond the acoustic diffraction limit in deep tissue via ultrasound-switchable NIR fluorescence

Abstract: Fluorescence imaging in deep tissue with high spatial resolution is highly desirable because it can provide details about tissue's structural, functional, and molecular information. Unfortunately, current fluorescence imaging techniques are limited either in penetration depth (microscopy) or spatial resolution (diffuse light based imaging) as a result of strong light scattering in deep tissue. To overcome this limitation, we developed an ultrasound-switchable fluorescence (USF) imaging technique whereby ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 30 publications
(42 reference statements)
0
66
1
Order By: Relevance
“…The FWHM of the transducer’s lateral acoustic profile was defined by the lateral focal size of the HIFU transducer (with a central frequency of 2.5 MHz and f-number of 0.83), which was measured ~0.42 mm. The estimated FWHM of the PSF (~0.9 mm) is ~2 times larger, larger also than what we have observed in our previous continuous wave (CW) mode system (0.29 mm) [13]. Current USF resolution is ~2 times worse than the lateral acoustic focal size of the HIFU transducer and ~3 times worse than the resolution our previous study reported, where we had adopted a CW mode system.…”
Section: Discussioncontrasting
confidence: 48%
See 4 more Smart Citations
“…The FWHM of the transducer’s lateral acoustic profile was defined by the lateral focal size of the HIFU transducer (with a central frequency of 2.5 MHz and f-number of 0.83), which was measured ~0.42 mm. The estimated FWHM of the PSF (~0.9 mm) is ~2 times larger, larger also than what we have observed in our previous continuous wave (CW) mode system (0.29 mm) [13]. Current USF resolution is ~2 times worse than the lateral acoustic focal size of the HIFU transducer and ~3 times worse than the resolution our previous study reported, where we had adopted a CW mode system.…”
Section: Discussioncontrasting
confidence: 48%
“…Fig 1(f) shows how their fluorescence intensity switches according to temperature; S1 Table provides a summary of those contrast agents. Impressively, all the intensity ratios (I ON /I OFF ) are >200, while previously developed agents have I ON /I OFF <10 [13],[15],[16],[20]. Fig 1(g) and 1(h) show that the switching property from ADP(CA) 2 -encapsulated Pluronic-F127 nanocapsules has excellent stability and repeatability.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations